Two cases of congenital dermatomyofibroma. Issue 4 (21st June 2021) - Brooks, Blake Elizabeth; Robinson‐Bostom, Leslie; Telang, Gladys; Bercovitch, Lionel
Abstract: We present two infants with histologically confirmed congenital dermatomyofibromas. Congenital cases are rare with only one prior case reporting presence since birth. Given the benign nature of the lesions and propensity of dermatomyofibromas to resolve without intervention in young male patients, no additional treatments were pursued.